Прогрммный генератор телефонной нагрузки для тестирования voip шлюзов - Бондаренко, К. И. (ХНУРЭ, 2009)
Voice communications have been growing within Research and Education institutions for several years, based on new and popular SIP protocols. SIP (Session Initiation Protocol) is the IETF standard for the establishment of multimedia sessions. These sessions might be used for audio, video, instant messaging or other real-time data communications sessions.
Keywords: тестирование voip шлюзов; генератор телефонной нагрузки